Physical Modelling of Pile-group effect on the Local Scour in Submarine Environments. (2016) - Li, Yi-Xuan; Qi, Wen-Gang; Gao, Fu-Ping
Abstract: Pile groups are extensively utilized to provide stability of offshore structures and bridges across rivers. Under the actions of waves and current, severe local scour can be induced around the pile groups in cohesionless soils, compromising the safety of structures significantly. An accurate prediction of local scour depth is difficult because the three-dimensional flow around pile groups is a complicated process. A series of flume tests were conducted in a novel water flume for flow-structure-soil interaction modelling, to investigate the local scour process around twin-pile groups. Two different hydrodynamic loading conditions, i.e., current alone and current plus waves, were adopted in the tests. The effects of the hydrodynamic loading conditions and the influence of the twin-pile layout on the scour have been investigated. It was found that compared with the maximum scour depths around a single pile, those around tandem twin-pile groups are generally a bit smaller while those around side-by-side twin-pile groups are remarkably larger, especially for the cases with small pile spacing. The observed maximum scour depth around side-by-side twin-pile groups with no separation can be nearly twice of that around a single pile. For the side-by-side arrangement, there is a qualitative agreement between the present results and the results of the preceding studies.